Identification of several fractions of patchouli alcohol from patchouli oil (Pogostemon cablin Benth.) using combination method of infrared spectroscopy and principal component analysis - Puji Astuti,; Khairan,; Marthoenis,; Hasballah, Kartini (Penerbit Universiti Kebangsaan Malaysia, 2022)
Patchouli oil is a type of essential oil that is very popular all over the world because it is rich in benefits and has high economic value as well. The quality of it must be maintained and strictly controlled to prevent counterfeiting. In this study, the patchouli oil sample used was Aceh patchouli oil of the Tapak Tuan variety, Indonesia. The patchouli oil was redistilled and crystallized to obtain 5 varying levels of patchouli alcohol. This study aims to evaluate the application of chemometrics and Fourier transforms infrared (FTIR) spectroscopy as simple, effective and economical methods to assess the quality of patchouli oil and patchouli crystals. FTIR data from the 5 samples were subjected to multivariate analysis consisting of Hierarchical Cluster Analysis (HCA), Principal Component Analysis (PCA) and Linear Discriminant Analysis (LDA). HCA, PCA and LDA managed to distribute the tested samples into informative groups. The results of the HCA analysis showed the pattern of sample classification based on patchouli oil concentration, the results of the PCA analysis showed that the PCA plot scores were quite adequate in distinguishing patchouli oil concentrations. The results of the LDA analysis showed the authenticity of the patchouli oil spectrum based on the results of PCA analysis. From the cross-validation accomplished, this method was successful in predicting accurately the concentration of patchouli oil samples. The results of the analysis concluded that the combination of the FTIR-Chemometric method is a fast, easy, accurate and inexpensive method. In addition, this analysis can be executed without damaging the sample.